Recent Studies on Nanomaterials as Additives to Lubricants Under Electrified Conditions for Tribology: Review - Khodor Nasser; María J. G. Guimarey; Neuma das Mercês Pereira (Lubricants)
The tribological performance of nanolubricants in electric drivetrains has gained attention due to the rapid growth of electric vehicles. Nanomaterials, especially those with high thermal conductivity and low electrical conductivity, are favored as lubricant additives for use in electrical conditions. Low-viscosity lubricants, known for their good thermal conductivity, are increasingly being considered for electric powertrains. Combining appropriate nanomaterials with lubricants can optimize nanolubricants for electric drivetrains, with stability, tribocorrosion, and electro-viscosity being key factors. Traditional tribometers, when modified to apply external electrical power, allow testing of nanolubricants under electrical conditions, providing insights into their behavior with positive and/or negative electrical charges. To achieve accurate and stable results, tribological test systems must be adapted, requiring well-isolated rigs for controlled data collection. This adaptation enables a better understanding of the interaction between nanomaterials and surfaces under lubrication. This paper reviews studies that use modified tribometers to analyze nanolubricant performance under mechanical and electrical conditions and explores the effects of electrical and thermal factors on lubricant properties, nanomaterials, and their mechanisms under triboelectric conditions.